The Ability of Microbial Community of Lake Baikal Bottom Sediments Associated with Gas Discharge to Carry Out the Transformation of Organic Matter under Thermobaric Conditions - Bukin, Sergei V.; Pavlova, Olga N.; Manakov, Andrei Y.; Kostyreva, Elena A.; Chernitsyna, Svetlana M.; Mamaeva, Elena V.; Pogodaeva, Tatyana V.; Zemskaya, Tamara I. (Frontiers in Microbiology, 2016)
The ability to compare the composition and metabolic potential of microbial communities inhabiting the subsurface sediment in geographically distinct locations is one of the keys to understanding the evolution and function of the subsurface biosphere. Prospective areas for study of the subsurface biosphere are the sites of hydrocarbon discharges on the bottom of the Lake Baikal rift, where ascending fluxes of gas-saturated fluids and oil from deep layers of bottom sediments seep into near-surface sediment. The samples of surface sediments collected in the area of the Posolskaya Bank methane seep were cultured for 17 months under thermobaric conditions (80°С, 5 MPa) with the addition of complementary organic substrate, and a different composition for the gas phase. After incubation, the presence of intact cells of microorganisms, organic matter transformation and the formation of oil biomarkers was confirmed in the samples, with the addition of Baikalian diatom alga Synedra acus detritus, and gas mixture СH4:H2:CO2. Taxonomic assignment of the 16S rRNA sequence data indicates that the predominant sequences in the enrichment were Sphingomonas (55.3%), Solirubrobacter (27.5%) and Arthrobacter (16.6%). At the same time, in heat-killed sediment and in sediment without any additional substrates, which were cultivated in a CH4 atmosphere, no geochemical changes were detected, nor the presence of intact cells and 16S rRNA sequences of Bacteria and Archaea. This data may suggest that the decomposition of organic matter under culturing conditions could be performed by microorganisms from low-temperature sediment layers. One possible explanation of this phenomenon is migration of the representatives of the deep thermophilic community through fault zones in the near surface sediment layers, together with gas-bearing fluids.